Analisis Wacana Kritis Theo Van Leeuwen Pada Ebook Sejarah Penggusuran di Jakarta Era Tahun 1970-1980: Tempo Publishing - Zeni Ayu Ariani; Aprilia Kartika Putri; Ernanda Ernanda (Kajian Linguistik dan Sastra, 2023)
This study aims to find out how the forms of inclusion and exclusion strategies contained in the news ebook History of Evictions in Jakarta in the 1970-1980 era: Tempo Publishing. This research used a qualitative approach with a descriptive literature review model. Researchers download ebooks, and purchase ebooks contained in the Google Play Book application. The data in this study are words, phrases, news sentences published by Tempo publishing. Researchers found as many as 69 exclusion and inclusion data. The exclusion strategy aims to see how actors are excluded from the text of the conversation. The exclusion strategy contained 36 data. The data is divided into 28 passivation process data and 8 nominalization process data. Then forms of inclusion strategy which aims to see how actors are included in the text of the conversation, found as many as 33 data. The data is divided into 2 nomination process data, 9 categorization data, 5 objectivation data, 3 determination data, 6 indetermination data, and 8 association data. From the results of the study it can be concluded that there are more constructions that obscure actors in events, compared to constructions that highlight actors. Topics that eliminate or obscure actors are about evictions and discrimination against marginalized people, while topics that give rise to actors are about the suffering of marginalized people. Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana bentuk strategi inklusi dan eksklusi yang terdapat dalam ebook berita Sejarah Penggusuran di Jakarta era tahun 1970-1980:Tempo Publishing. Penelitian ini menggunakan pendekatan kualitatif dengan model kajian studi pustaka yang bersifat deskriptif. Peneliti mengunduh ebook, dan melakukan pembelian ebook yang terdapat pada aplikasi google play book. Data dalam penelitian ini adalah kata, frasa, kalimat berita yang diterbitkan oleh Tempo publishing. Peneliti menemukan sebanyak 69 data eksklusi dan inklusi. Strategi eksklusi bertujuan untuk melihat bagaimana aktor dikeluarkan dari teks pembicaraan. Strategi eksklusi terdapat 36 data. Data tersebut terbagi menjadi 28 data proses pasivasi dan 8 data proses nominalisasi. Kemudian bentuk-bentuk strategi inklusi yang bertujuan untuk melihat bagaimana aktor dimasukkan dalam teks pembicaraan, ditemukan sebanyak 33 data. Data tersebut terbagi menjadi 2 data proses nominasi, 9 data kategorisasi, 5 data objektivasi, 3 data determinasi, 6 data indeterminasi, dan 8 data asosiasi. Dari hasil penelitian dapat disimpulkan bahwa terdapat lebih banyak kontruksi yang mengaburkan aktor dalam peristiwa, dibandingkan konstruksi yang menonjolkan aktor. Topik-topik yang menghilangkan atau mengaburkan aktor adalah mengenai penggusuran dan diskriminasi pada kaum marginal, sedangkan untuk topik-topik yang memunculkan aktor adalah mengenai penderitaan pada kaum marginal.